Pediatric hematology and oncology physician and nurse practitioner views of the HPV vaccine and barriers to administration - Meagan E. Miller; Mahvish Q. Rahim; Scott L. Coven; Seethal A. Jacob; Gregory D. Zimet; Carolyn G. Meagher; Mary A. Ott (Taylor & Francis Group, 2023)
Rates of Human papilloma virus (HPV) vaccination among pediatric survivors of cancer and patients with sickle cell disease are lower than the national average. While recent attention has focused on patient HPV vaccine hesitancy and refusal, less is known about provider-level and system-level barriers to vaccinations in pediatric hematology/oncology (PHO) populations. Applying thematic analysis to qualitative interviews with 20 pediatric hematology/oncology physicians and nurse practitioners, we examine their views regarding HPV vaccination, with a focus on access and barriers to providing HPV vaccination in PHO practices. Results demonstrated that despite 90% of interviewees supporting HPV vaccination in their population, the number of pediatric hematology/oncology providers who reported that they counsel about HPV or provide HPV vaccination was 45%, even in stem cell and sickle cell clinics, where other childhood vaccines are commonly provided. Clinicians identified provider-level, clinic-level, and system-level barriers to giving the HPV vaccination, including but not limited to time/flow constraints, lack of resources, and continued education regarding the HPV vaccine. These barriers impede the ability for pediatric hematology/oncology providers to counsel and provide HPV vaccination to this specialized population.